Respiratory infections and immune biomarkers of infection and inflammation in cases of Sudden Unexpected Death in Infancy (SUDI) at the Tygerberg Medico-legal Mortuary - Matshazi, Don Makwakiwe (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMedSc)--Stellenbosch University, 2018.